2017
DOI: 10.1002/mc.22701
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid induces thioredoxin1‐mediated apoptosis in lung cancer cells via up‐regulation of miR‐129‐5p

Abstract: Histone deacetylase (HDAC) inhibitors, especially suberoylanilide hydroxamic acid (SAHA) induce apoptosis in various cancer cells. Here, we investigated the effect of SAHA on apoptosis in lung cancer cells and addressed the role of reactive oxygen species (ROS), glutathione (GSH), and thioredoxin1 (Trx1) levels in this process. We also identified the miRNAs that down-regulate Trx1 expression at RNA level and thereby influence apoptotic cell death of SAHA increased intracellular ROS levels and promoted apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 48 publications
(116 reference statements)
1
11
0
Order By: Relevance
“…Ectopic expression of HIF1A-AS2 suppressed miR-129-5p expression in MG-63 cells. Several studies have suggested that miR-129-5p plays important roles in the development of tumors such as hepatocellular carcinoma, colon cancer, breast cancer, lung cancer, gastric cancer and osteosarcoma [43][44][45][46][47][48]. Long et al [48] showed that miR-129-5p expression might be regulated by demethylation and that miR-129-5p suppressed osteosarcoma cell invasion and migration by targeting valosin-containing protein (VCP) in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of HIF1A-AS2 suppressed miR-129-5p expression in MG-63 cells. Several studies have suggested that miR-129-5p plays important roles in the development of tumors such as hepatocellular carcinoma, colon cancer, breast cancer, lung cancer, gastric cancer and osteosarcoma [43][44][45][46][47][48]. Long et al [48] showed that miR-129-5p expression might be regulated by demethylation and that miR-129-5p suppressed osteosarcoma cell invasion and migration by targeting valosin-containing protein (VCP) in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors, such as suberoylanilide hydroxamic acid (SAHA), have been shown to induce apoptosis in various cancer cells by increasing the production of ROS [188,189]. You et al [190] found that miR-129-5p was upregulated by SAHA-treatment in cancer cells and, at least in part, mediated ROS increased production by targeting the antioxidant protein thioredoxin1 (Trx1). More recently and in line with this, miR-129-5p has been shown to function as a tumor suppressor when overexpressed in lung cancer cells [191].…”
Section: Mir-155 and Oxidative Stress In Cardiac And Pulmonary Diseasesmentioning
confidence: 99%
“…With the deepening of miRNA research, targeting their downstream genes to regulate multidrug resistance has become a research hotspot. MiR-129-5p, a tumor inhibitor, has been validated to inhibit cancer cells migration, proliferation, differentiation, and epithelial-mesenchymal transition (17 20). In addition, miR-129-5p-mediated beclin-1 suppression inhibits endothelial cell autophagy in atherosclerosis (21).…”
Section: Introductionmentioning
confidence: 99%